Sistem Monitoring Kondisi Kelembapan dan pH Tanah Berbasis Internet of Things (IoT) untuk Tanaman Hias - Cahyono, Bayu Adi; Akbar, Yuma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Manual monitoring of soil moisture and pH often hinders the growth of ornamental plants, posing a challenge for hobbyists. This study addresses this issue by developing an Internet of Things (IoT) based monitoring system using a Research and Development (R&D) method. A functional prototype was built with an ESP32 microcontroller, a capacitive moisture sensor, and a pH sensor, which transmits real-time measurement data to the Blynk mobile application. Following a systematic sensor calibration process, test results confirmed the system's ability to accurately and responsively present moisture and pH data. All system functionalities, from data visualization to notifications, were successfully verified. The system is proven to be a functional and practical solution, enabling users to shift from intuitive care to precise, data-driven maintenance for optimal plant growth.